Analisis Perilaku Fear of Missing Out (FoMO) di Instagram dalam Perspektif Hadis - Fahmi Azzaki; Uswatun Hasanah; Sulaiman Muhammad Nur (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
FoMO (Fear of Missing Out) is a psychological condition that reflects anxiety or fear of missing out on information, experiences or opportunities that other people have. This phenomenon often influences the behavior of social media users, especially on platforms like Instagram, where they are encouraged to spend time and energy following trends and viral information. As a result, users often lose track of time and sacrifice their real social life. This research aims to analyze FoMO behavior on Instagram from the perspective of hadith in Islam. The research method used is qualitative, with a literature study approach and digital content analysis on several Instagram accounts, such as @folkative, @indozone.id, and @jakarta.keras. Hadiths of the Prophet Muhammad SAW that are relevant to the FoMO theme are used in this research. The research results show that FoMO can have a negative impact on the social life, mental health and spirituality of Instagram users. FoMO causes excessive feelings of dissatisfaction, anxiety, and stress. However, the hadiths of the Prophet Muhammad SAW provide guidance for a Muslim to overcome anxiety and fear of missing out. Hadith about gratitude, qana'ah (satisfaction with what one has), and tawakkal (trust in Allah) can be a solution to overcome excessive FoMO. On the other hand, FoMO also has positive impacts, such as generating motivation and increasing a person's creativity when managed wisely. By understanding and applying the values taught in the hadith, users can reduce the negative impacts of FoMO and take advantage of its positive impacts.